Features of the interrogation tactics of a suspect in illegal fishing, hunting, or other aquatic resource exploitation - R. O. Stadnichenko (Bulletin of Kharkiv National University of Internal Affairs)
The article discusses interrogation tactics of a suspect involved in illegal fishing, hunting, or other aquatic resource exploitation, necessitating the formation of specific tactical recommendations regarding the conduct of interrogations of suspects in criminal proceedings of this category. Based on an analysis of pre-trial investigation practices and scientific literature, the author proposes detailed specifications of the main provisions of interrogation tactics of suspects during the investigation of illegal fishing, hunting, or other aquatic resource exploitation.